2023
DOI: 10.1007/s11033-023-08539-6
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomics in stress tolerance of plants under the climate change

Abstract: During development and environmental stresses, plants experience genome-wide epigenetic alterations that are typically associated with differentiation in transcriptional gene expression.An epigenome is the aggregate of a cell's biochemical modi cations in its nuclear DNA, post-translational changes in histones, and differences in non-coding RNAs' biogenesis. Differences in gene expression that take place without any change in the underlying nucleotide sequence are frequently caused by these changes. Chromatin … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 179 publications
(93 reference statements)
0
7
0
1
Order By: Relevance
“…Epigenetic regulation of secondary metabolism: Plants have developed a sophisticated defense mechanism that utilizes secondary metabolites, such as phenolic compounds and alkaloids, against potential threats from pathogens and herbivores. Emerging research suggests epigenetic regulation also plays a crucial role in producing these compounds [ 154 , 155 , 156 ]. Specifically, studies demonstrate that DM and histone modifications improve the gene modification that produces anthocyanins, a particular phenolic compound that safeguards plants from UV radiation and oxidative stress [ 44 , 154 ].…”
Section: Recent Discoveries Of Plant Epigenetic Regulation In Respons...mentioning
confidence: 99%
See 3 more Smart Citations
“…Epigenetic regulation of secondary metabolism: Plants have developed a sophisticated defense mechanism that utilizes secondary metabolites, such as phenolic compounds and alkaloids, against potential threats from pathogens and herbivores. Emerging research suggests epigenetic regulation also plays a crucial role in producing these compounds [ 154 , 155 , 156 ]. Specifically, studies demonstrate that DM and histone modifications improve the gene modification that produces anthocyanins, a particular phenolic compound that safeguards plants from UV radiation and oxidative stress [ 44 , 154 ].…”
Section: Recent Discoveries Of Plant Epigenetic Regulation In Respons...mentioning
confidence: 99%
“…Epigenetic regulation of stem cell maintenance: Stem cells are essential for the germination of plants and stress response, and recent research has shown that epigenetic regulation is included in stem cell maintenance. For example, studies have found that DM and HM are involved in the influence of stem cell fate decisions in Arabidopsis thaliana [ 12 , 25 , 156 ].…”
Section: Recent Discoveries Of Plant Epigenetic Regulation In Respons...mentioning
confidence: 99%
See 2 more Smart Citations
“…Many types of ncRNAs have been implemented in the direct or indirect regulation of various mechanisms of stress response and acclimation [133]. In this review, only the aspects of the involvement of siRNAs in RdDM will be covered, as this mechanism is the most likely to be involved in the establishment of somatic memory of stress exposures.…”
Section: Role Of Sirnas and Rddm In Stress Responsementioning
confidence: 99%